Malba Tahan e a revista Al-Karismi: diálogos e possibilidades interdisciplinares com a história da educação matemática no ensino fundamental - Costa, Leonardo Silva (2015)
This study, of qualitative nature, aims to contribute to the contextualization of mathematics and history of mathematics education in the teaching and learning of this science from didactic and pedagogical proposals inspired by the teacher's speech Júlio Cesar de Mello e Souza the Malba Tahan the primary source Al-Karismi (1946-1951). The research, on the one hand, proposes a study that source and secondly, a dialogue with educational possibilities for teaching mathematics in elementary school, involving the History of Mathematics Education in an interdisciplinary perspective, using the instruments of Sheets Work and Reporting Assessment with students of the 8th grade of elementary school to a public school in the city of Ituiutaba / MG, articulating aspects that favored teaching and interdisciplinary learning in mathematics. Intended to present results of applying six didactic proposals designed to research, with the analysis of the survey axis categories defined a priori by the possible learning situations in the service of the History of Mathematics, related to the speech of students. The study found that students were involved more with practice teacher, listing some of the terms tahaniano speech to the knowledge built in the classroom. It is believed that the proposal collaborated to build a research environment conducive to the mathematical thinking, its relations with the socio-cultural context of the students and the use of history as a resource that guided and promoted the understanding of subject content, tangential interdisciplinary themes, legitimizing the voice of students as subjects members in the process of teaching and learning and making maths fun, curious and pleasant, in malbatahanico style of being.